Peran Satgas Haji dalam Peningkatan Kualitas Pelayanan Jemaah Lansia di Asrama Haji Donohudan - Fatiha, Siti Nuriya Ulha; Affandi, Yuyun; Darissurayya, Vina; Rozaq, Abdul; Malik, Hatta Abdul (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to analyze the role and challenges faced by the Hajj Task Force in serving elderly pilgrims at Donohudan Embarkation. The main challenges that the task force often faces when serving elderly pilgrims include effective communication, physical handling of the elderly which requires extra energy, and building the trust of elderly pilgrims who are often hesitant to accept help. Another difficulty is guiding elderly people who are senile to follow procedures. The research method uses qualitative research with a descriptive approach. Data collection techniques used in-depth interviews, participatory observation, and documentation. The informants in this study were selected using the Snowball Sampling technique, in this technique the researcher starts with one or two individuals, then they recommend other individuals to be sampled. The results show that although the facilities at Donohudan Embarkation are adequate, some shortcomings still exist, especially in terms of facilities for the disabled and elderly. The biggest challenges faced by the Task Force in serving elderly pilgrims are communication, physical handling that requires extra energy, and building trust from elderly pilgrims who are often hesitant to accept help. This research contributes to improving the quality of Hajj services, especially for elderly pilgrims.